Implementación de un control electrónico, para la automatización de un grupo electrógeno de emergencia y sistema de transferencia automática en una granja avícola de codornices. - Ludeña Jiménez, Milton Eduardo (2015)
The quail farm Golden Eggs , located in the canton Catamayo in the province of Loja, keeps a constant production of eggs and quail meat. In this production line it is integrated; egg incubation grinding raw material, poultry feed production, to others lighting batteries for posture birds; for which it is required a constant electrical power supply. For this purpose it is mounted an emergency power diesel engine that mitigates the energy requirements to facilities eventual against power outage. Then it proceeds to the automation Generator to comply with the following requirements: • The On and Off the GE front of an outage of the commercial network and return it. • Monitoring of variables of the engine and generator for a normal operation. • Implement and monitor the process of transfer and retransfer of the load. For this purpose we use an electronic control ComAp IL-AMF 20, the same as is programmed according to the characteristics of the generator and automatic transfer. The control works with a supply voltage of 12 VDC from the engine battery, the electronic control is appropriate for this purpose because in the attempt to start the engine, battery feels up to 8 VDC and the electronic control keeps on your operation, at the same time is installed battery maintainer which keep the level of battery charge in moments of inoperability of the generator. They are installed the electrical protection and control force of the agreement demand load current, power generator and electronic control functionality. Operating equipment is maintained on the basis of demands and following preventive maintenance schedule.